435 Single Session CBT to Improve PAP Initiation and Adherence among Veterans with OSA. (3rd May 2021) - Bishop, Todd; Walsh, Patrick; Stecker, Tracy; Speed, Katrina; Ashrafioun, Lisham; Stepnowsky, Carl; Kuna, Samuel; Pigeon, Wilfred
Abstract: Introduction: Obstructive sleep apnea (OSA) is a condition that is prevalent, pernicious, and linked to the development and exacerbation of several disease processes. Positive airway pressure (PAP) is a highly efficacious intervention; however, initiation and adherence rates are poor. This represents a critical gap in care and a missed opportunity to reduce morbidity and mortality associated with OSA. The present study piloted a single session of cognitive behavioral therapy for treatment seeking (CBT-TS) among veterans diagnosed with obstructive sleep apnea and newly prescribed PAP. Methods: Participants were asked to complete assessments at baseline and at two- and four-weeks post-intervention. A sample of 40 Veterans were enrolled in the study and completed a baseline interview, 27 completed CBT-TS. A matched comparison group of 64 veterans who did not receive the intervention was constructed using electronic medical record and PAP adherence data. Mann Whitney U and Chi Square tests were used to examine group differences in initiation and adherence. Results: Participants who completed the CBT-TS session were more likely to initiate PAP (at least 3 consecutive nights of use) as compared to those receiving treatment as usual (TAU) [(CBT-TS; 96.3%; 26/27) versus (TAU; 64.1%; 41/64); X2(1, N = 91) = 10.16, p = .001]. Participants in the CBT-TS group also used their PAP devices for a greater number of nights over the first month than the comparison group [(CBT-TS; M = 21.7 (SD = 8.9), Mdn = 26.0) versus (TAU; M = 14.4 (SD = 12.6), Mdn = 15.5); U = 555.0, p = .007] and were more likely to use the device in an adherent manner (i.e., ≥4 hours use in an evening); [(CBT-TS; M = 15.1 (SD = 11.2); Mdn = 15.0) versus (TAU; M = 10.3 (SD = 11.2), Mdn = 6.5); U =630.0, p = .038]. Conclusion: These preliminary data suggest that CBT-TS may have utility in increasing initiation of PAP and subsequent treatment adherence among Veterans diagnosed with OSA and newly prescribed PAP. Support (if any): This work was supported by the VA Center of Excellence for Suicide Prevention in the Finger Lakes Healthcare System.